Perkembangan Islam di Brunei - Fikria Najtama (LPPM IAIN Sorong, 2018)
Brunei has existed since at least the 7th or 8th century. In the history mentioned Islam has come to Brunei since the 7th century, which at that time Brunei has become a center of trade. The king of Brunei Malay kingdom since Sultan Muhammad Shah (1383), is a Muslim sultan who leads the kingdom as well as religious leaders, and is responsible for upholding the implementation of religious teachings in the region. This paper will discuss the development of Islam and the dynamics of Malay politics, religion and traditions in Brunei Darussalam to the present, including how Brunei Islam can pass through the British colonial era with unique conditions, even as they respect Britain as the savior of their country. Brunei reached its heyday from the fifteenth to the seventeenth century at the time of the Bolkiah Sultan, who ruled the entire island of Borneo and the Philippine archipelago, before the arrival of European colonial nations. Together with Malaysia, Brunei was colonized by Britain, and since 1888 the Kingdom of Brunei is a British Commonwealth. After Malaysia Merdeka (1957), Brunei declared its independence on January 1, 1984 from Malaysia. Although not a vast country. Brunei is an Islamic state that plays an important role in maintaining Islamic values in society. This is the success of the mosque coaching program and the advancement of religious education as a top priority. The Malay Muslim Kingdom of Brunei Darussalam made Islam its national ideology to implement Sunni Islam (Ahlussunnah Waljamaah), to obey the king, and to live the life of Darussalam as a Malay nation In fact, all the activities of the kingdom and government rules serve to strengthen the existence of Islam. The threat of Islam that can disrupt the stability of the country is a radical movement. The government has banned sectarian Islamic sects such as al-Arqam and others, so that Brunei remains a Darussalam, a safe, prosperous country, and protected from disturbances and chaos.